The Implications of Low Income Levels on Meeting Family Needs from the Perspective of Household Heads: A Field Study in the City of Zuwara (Al-Farooq Journal of Sciences, 2026)
The research aimed to study the impact of low income levels on families from economic, social, and psychological perspectives, as well as to explore coping strategies employed to improve living standards and achieve family stability. The study utilized a descriptive-analytical approach to collect and analyze data related to economic conditions, income levels, education, health, family stability, and coping strategies.The research was conducted on a sample of 150 household heads, randomly selected to represent various age groups and educational levels. The sample included age groups under 30 and over 60 years old, with educational levels ranging from below average to university and above.A standardized questionnaire was used to collect and analyze the data, and descriptive statistical methods were applied to determine percentages and frequencies for each research dimension, including economic conditions and income levels, education and health, family stability, and economic coping strategies.The results showed that low income imposes financial and psychological pressure on families and affects their ability to meet basic needs such as food, housing, education, and healthcare. It also increases family conflicts and limits social cohesion. At the same time, families resort to various coping strategies, including rationalizing consumption, increasing working hours, diversifying income sources, with limited reliance on external aid.The study concluded that low-income pressures have interrelated effects on quality of life and family stability, necessitating interventions to support families financially and socially. Recommendations included enhancing financial and social support programs, providing subsidized education and healthcare, launching small family projects, implementing financial management training programs, conducting awareness campaigns to strengthen family cohesion and reduce conflicts, and developing sustainable community support networks.
Keywords: income level, needs, family, heads of households, Zuwara city